Sopra un frammento del giovane Kafka. Modi della Vorstellung (Materiali di Estetica. Terza serie, 2017)
As the title suggests the Brod-Kafka controversy demonstrates how difficult it is to distinguish wishful perceptions from reality-testing. The contribution investigates therefore what is here being called ways of the Vorstellung in relation to a Freudian theory of representation. In particular Vorstellungsrepräsentanz (representative of the presentation) denounces the problematic functioning of representational processes where language is involved. Dealing with ethical questions, Kafka’s early production illuminates the paradox of subjectivity involved in writing. In this in-Between space (Dazwischen) language and Vorstellung (Vorstellungsrepräsentanz) are not intended to guarantee communication. This hinges upon Kafka’s narrative strategies which consider living bodies as generating a dialectic of accommodation and excess not to be exhausted by ideas and schematas. Kafka’s early prose Description of A Struggle as well as the strange devices he conceives while lying in bed, at rest or sleepless illustrate the point. In terms borrowed from Lacans’ Seminar VII Kafka’s answers along with the prose of this period denounce the limits and the deceptive origin of apperception as related to consciousness and the ego. The aesthetical dimension, intertwined with the psychogenesis of the body proper, leads to unprecedented ethical challenges. Representation does not only mediate the knowledge we consume (“ästhetische Freude” – “Apperception”), it also affects knowledge so that we assume with Kafka that representation constructs knowledge. This is also why the Bionian grid as filtering transformational device is compared to Kafka’s description of himself as a lattice-work-man, a trellis. The will we are willing to investigate and cope with in Kafka’s semi-oneiric productions is a poetic will defying figuration. Emerging by means of stylistic and rhetorical strategies this will disconfirms any systematized mental connection aimed at classifying, explaining, understanding. The idea of Vorstellung Kafka maintains challenges our assumptions; it shows how the external world, which is generally understood as the mediation of the perceptual, is overdetermined by our emotions, unconscious desires, affections.KEYWORDS: Unconscious representation as unavailable vs apperception; “in-Between” space; the grid (Bion); “having enough of something”; pleasure principle vs aestethic enjoyment; writing process as working through of experience vs deceptive representational mechanisms